Pilar kebangsaan di era globalisasi - dessiantoro, yoggy zora (Maliki Interdisciplinary Journal, 2025)
The increasingly rapid development of globalization has had a significant impact on the perspective and behavior of Indonesian society. The openness of the flow of information, culture, and global technology requires the Indonesian people to remain grounded in the four pillars of nationality, namely Pancasila, the 1945 Constitution, the unitary State of the Republic of Indonesia (NKRI), and Bhineka Tunggal Ika. These four pillars serve as guidelines in maintaining national identity, unity, and resilience amidst changing times. This study aims to reexamine the meaning and application of the pillars of nationality in the context of modern life. The results of the study indicate that strengthening the values of Pancasila and the spirit of diversity is key to building a strong national character, integrity, and global competitiveness. The pillars of nationality not only serve as a legal and moral basis, but also serve as a foundation for strengthening national identity so that the Indonesian nation remains firmly established as a sovereign nation with personality amidst the complex currents of globalization.